The Use of Mentoring in Uplifting EFL Students’ Self-Regulated Language Learning in Speaking - Muchlisha, Tita; Halim, Abdul; Syukri, Suhartini (IAIN KENDARI, 2025)
This study examined the impact of mentoring programs on EFL students’ self-regulated language learning as a strategy utilized in their speaking processes. Qualitative methodology was employed in this research. The study involved 15 EFL students who participated in a mentoring program with at least 3 meetings. Data were collected from students’ written reflections using Google Forms, which were then distributed through a WhatsApp Group. The researcher analyzed the data using thematic coding. The analysis revealed significant positive changes in students’ self-regulated learning through mentoring, including expanding ideas, enriching vocabularies, building critical thinking, developing self-confidence, enhancing motivation, increasing awareness of learning, and creating a positive mindset. This study suggests that both teachers and students should consider implementing mentoring as an effective strategy for developing self-regulated learning in a speaking context. Keywords: Learning Speaking, Self-Regulation, Mentoring